Finite-Time LOS Path Following of Unmanned Surface Vessels With Time-Varying Sideslip Angles and Input Saturation - Yu, Yalei; Guo, Chen; Li, Tieshan (IEEE/ASME transactions on mechatronics, 2022)
In this article, a finite-time line-of-sight-based control (FTLC) scheme is presented for path following of unmanned surface vessels (USV) subject to unknown time-varying sideslip angles and input saturation as well as uncertainties induced by unknown internal dynamics and external disturbances. Specifically, finite-time observers (FTOBs) are introduced to acquire the sideslip angle and kinetic uncertainties. Finite-time line-of-sight guidance is developed by incorporating the FTOB and fractional power techniques. The profile of desired surge velocity is designed based on the hyperbolic tangent function of cross-track error. Nonlinear feedback is then introduced to attenuate the overshoot of surge velocity. Finite-time stability auxiliary systems are designed using fractional power to compensate for actuator constraints with finite-time convergence. The proposed FTLC scheme enables a USV to reach and follow a predefined path while satisfying spatial and dynamical specifications and obtaining finite-time stability and small overshoot in the presence of actuator limitations and uncertainties. All errors in the closed-loop system of USV converge to an arbitrarily small neighborhood of the origin within a finite settling time, which still holds in the presence of unpredictable errors. Three USV cases and ten simulation groups are included to demonstrate the effective performance of the FTLC.